Quantum annealing research at CMU: algorithms, hardware, applications - Tayur, Sridhar; Tenneti, Ananth (Frontiers in Computer Science, 2024)
In this mini-review, we introduce and summarize research - at Quantum Technologies Group (QTG) at Carnegie Mellon University, in collaboration with several other institutions, including IIT-Madras and NASA (QuAIL) - related to computational experience with quantum annealing. We present a novel hybrid quantum-classical heuristic algorithm (GAMA, Graver Augmented Multi-seed Algorithm) for non-linear, integer optimization, and illustrate it on an application (in cancer genomics). We then present an algebraic geometry based algorithm for embedding a problem onto a hardware that is not fully connected, along with a companion Integer Programming (IP) approach. Next, we discuss the performance of two photonic devices - the Temporal Multiplexed Ising Machine (TMIM) and the Spatial Photonic Ising Machine (SPIM)- on Max-Cut and Number Partitioning instances. We close with an outline of current work.